Subclavian Aneurysm Presenting with Massive Hemoptysis: A Case Report and Review of the Literature - Brown, Hilary A.; Aruny, John E.; Elefteriades, John A.; Sumpio, Bauer E. (International Journal of Angiology, 2013)
We present a case of a 70-year-old male with a past medical history of coronary artery bypass grafting and end stage renal disease who presented with massive hemoptysis. He had a history of methicillin-resistant Staphylococcus aureus endocarditis, with infection and removal of endocardial pacing leads. His work-up revealed a 2.9-cm proximal left subclavian artery aneurysm. Bronchoscopy confirmed bright red blood in the left upper lobe bronchus and coronary angiography confirmed a patent left internal mammary artery (LIMA) to left anterior descending bypass. Because of the consideration of maintaining coronary perfusion via the LIMA while excluding the subclavian aneurysm, he underwent a left carotid to left axillary artery bypass graft followed by deployment of an Amplatzer II vascular plug just distal to the aneurysm. A thoracic endograft was then deployed to exclude the origin of the subclavian. A review of the literature reveals hemoptysis as a rare presentation of a subclavian aneurysm. We discuss approaches to this challenging clinical problem, ranging from open repair to hybrid approaches.
Keywords: subclavian; aneurysm; hemoptysis; hybrid; endovascular repair